Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1089/vbz.2008.0184
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Tick-Borne Pathogens in Dogs from an Indian Reservation in Northeastern Arizona

Abstract: We evaluated the serological and molecular prevalence of selected organisms in 145 dogs during late spring (May/June) of 2005 and in 88 dogs during winter (February) of 2007 from the Hopi Indian reservation. Additionally, in 2005, 442 ticks attached to dogs were collected and identified as Rhipicephalus sanguineus. Infection with or exposure to at least one organism was detected in 69% and 66% of the dogs in May/June 2005 and February 2007, respectively. Exposure to spotted fever group (SFG) rickettsiae was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
2
47
1
1
Order By: Relevance
“…The sensitivity and specificity for E canis and B burgdorferi were similar to that reported for another ELISA from the same manufacturer. 15,[25][26][27] In the present study, we identified 68 of 846 canine samples that contained antibodies against > 1 species of tick-borne pathogen. A large number of samples with positive results for D immitis (as confirmed during necropsy or on the basis of results of the heartworm antigen test) were evaluated in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The sensitivity and specificity for E canis and B burgdorferi were similar to that reported for another ELISA from the same manufacturer. 15,[25][26][27] In the present study, we identified 68 of 846 canine samples that contained antibodies against > 1 species of tick-borne pathogen. A large number of samples with positive results for D immitis (as confirmed during necropsy or on the basis of results of the heartworm antigen test) were evaluated in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…More than 48 of 217 (22%) samples that were seroreactive for A phagocytophilum were also seroreactive for B burgdorferi. In a recent study, 27 investigators clarified that there can be borreliosis and anaplasmosis coinfection in dogs in defined endemic areas, whereas E canis and A platys generally are in different geographic locations. The prevalence of coinfection in dogs is caused by several factors, including sequential or cotransmission of organisms, the expanding range of the tick vectors, increased travel by pet owners accompanied by their dogs, and a tendency for families to move into tick-laden environments.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently [14], no subsequent report of human A. platys infection was published in the English literature. There is substantial epidemiological support for Rhipicephalus sanguineus (the brown dog or kennel tick) as the vector and the dog as the primary reservoir host for A. platys and E. canis [20]. As the puppy in this study originated from a kennel in Missouri, exposure to R. sanguineus seemed more likely than exposure to A. americanum, which is a field tick that will feed on numerous animal species [29].…”
Section: Discussionmentioning
confidence: 99%
“…Blots were washed thoroughly then incubated with alkaline phosphatase labeled anti-human IgG (γ chain-specific) secondary antibodies and color reactions developed with BCIP/NBT phosphatase substrate (KPL, Inc. Gaithersburg, MD). Serum from the dog was tested for Ehrlichia antibodies by IFA in the IPRL, using antigens derived from canine monocytic DH82 cultures infected with E. canis and E. chaffeensis and for Anaplasma or Ehrlichia antibodies using the Snap® 4Dx®, (IDEXX Laboratories Inc., Westbrook, Maine) [19,20]. …”
Section: Methodsmentioning
confidence: 99%
“…Some strains of E. chaffeensis have homologous proteins to E. canis and therefore cross-reaction can occur (O'Connor et al 2002(O'Connor et al , 2006. Similarly, the A. phagocytophilum peptide detects antibodies induced in dogs upon infection with A. platys (unpublished data; SNAP 4Dx Test kit insert; Diniz et al 2010). The C6 peptide for B. burgdorferi is very specific (Duncan et al 2004); cross-reactions with other infections are not known to occur.…”
Section: Methodsmentioning
confidence: 99%